Tradition of Gratitude (Slametan) before Starting a Business and Whening a Success: A Business Ethics Perspective in Pamekasan, Madura - Khoirun Nisa', Nafilatun; Fadllan, Fadllan (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study examines the practice of slametan tradition before starting a business and during business glory in Kadur Village, Kadur Subdistrict, Pamekasan Regency, in the perspective of Islamic business ethics. The slametan tradition carried out by the community involves reciting prayers, Al-Qur'an, tahlil, and giving alms (bherkat), and is believed to bring blessings and safety in business. The research used qualitative methods with observation techniques and interviews with business people in the village. The results showed that the slametan tradition has become a hereditary habit that is loaded with spiritual, social, and ethical values. This tradition reflects Islamic moral values such as gratitude, tawakal, almsgiving, respect for ancestors, and strengthening social relations. In the context of Islamic business ethics, this tradition is a form of integration between divine values and economic practices that are oriented towards the balance of the world and the hereafter.